Kebijakan Non Penal Terhadap Tindak Pidana Perjudian Online Yang Dilakukan Oleh Anak Dibawah Umur di Kecamatan Sungailiat Kabupaten Bangka - Puspitasari, Della; Agustian, Rio Armanda; Toni, Toni (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
Sungailiat District is an area with children as the biggest potential perpetrators in Bangka Regency in criminal acts, especially online gambling. So that efforts are needed that are considered appropriate and strategic to tackle the criminal act of online gambling by children, namely through non-punitive policies as an effort to prevent, control and deter before criminal acts occur. This study aims to determine the implementation of non-penal policies against online gambling crimes by minors and describe the obstacles and solutions in the implementation of non-penal policies against online gambling crimes committed by minors in Sungailiat District, Bangka Regency. This research uses empirical juridical method with legal identification approach. The results showed that non-punitive policies against online gambling crimes committed by children in Sungailiat District, Bangka Regency have been implemented in several forms, namely socialization / legal counseling, and x-banners and for the community in the form of cyber patrols, digital posters and radio broadcasts about the dangers of online gambling practices by several agencies, namely the Bangka Resort Police, Sungailiat Sector Police and Bangka District Attorney's Office. The obstacles and solutions are HR/APH overcome by cooperating with other parties, legal substance overcome by coordinating with the authorities and reporting to the Police Headquarters, Children / Community can be overcome by giving regular appeals, Culture is not responsive quickly overcome by self-evaluation and conducting socialization / counseling simply / just an appeal and Infrastructure facilities overcome by prioritizing dominating problems.